Taxonomic studies of Macrochelidae mites (Acari: Mesostigmata) and their potential use to control Stomoxys calcitrans and Musca domestica (Diptera: Muscidae) - Azevedo, Letícia Henrique de (2017)
The family Macrochelidae Vitzthum is one of the most abundant and diverse groups of predatory mites living in excrements or decomposing animals. Some species of this family have shown good potential as biological control agents. Stomoxys calcitrans L. is a serious problem that has been faced by cattle raisers in some Brazilian states, causing significant losses. Musca domestica L. may vector several pathogens that affect humans and animals. The aims of the study reported in this document were the preparation of a taxonomic catalog of the world macrochelid species, to determine the macrochelid species in microhabitats where the stable fly is usually found in commercial cow raising farms in São Paulo State, and to evaluate of the effect of different macrochelid species as control agents of harmful muscid flies. A total of 520 species of 23 genera are reported in the catalog. In total, 1359 specimens were collected from cow manure and litter in different regions of São Paulo State. These represented ten species of three genera and one new species, which was described. In laboratory tests, Macrocheles n. sp. presented higher predation and oviposition rates on larvae of S. calcitrans (23.8 larvae consumed and laid about 4 eggs per day, respectively). For Macrocheles n. sp., total immature development (egg-adult) was completed in 1.3 ± 0.01, 1.3 ± 0.01 and 1.5 ± 0.03 days on eggs of S. calcitrans and M. domestica and on Protorhabditis sp., respectively. Fecundity was higher on Protorhabditis sp. (77.2 ± 5.1 eggs/female) than on S. calcitrans (58.0 ± 5.9) and M. domestica (55.0 ± 5.3). Results of this study suggest that Macrocheles n. sp. is a promising biological control agent of S. calcitrans and M. domestica, and that it could be mass reared with the use of Protorhabditis sp. or eggs of M. domestica.